Effects of turmeric and garlic on blood cholesterol level - Muhammad Mustafizur Rahman Chowdhury; Shah Md. Moinuddin; Md. Kamrul Islam (Bangladesh Pharmacological Society, 2008)
This study has been attempted to investigate the effects of garlic and turmeric on blood cholesterol level. A total of 20 male guinea pigs of unknown breed weighing 400-600 g were randomly divided into four equal groups (A, B, C, D) with free access to food and water for 30 days. Three groups of animals (B, C and D) were fed either with turmeric or garlic supplemented basal diet and were defined as treated groups while remaining one group (A) was fed only with basal diet and considered control group. The body weight increased significantly (p<0.01) in all the animals with the advancement of age. The administration of turmeric or garlic or both reduced the blood cholesterol level of the animals significantly (p<0.01). At the end of the experiment, the animals were killed and liver was examined for gross and histological changes. Some gross lesions were identified in liver of treated animals but there were no histological changes.